Riparian vegetation response to clearcutting along small streams of boreal forest / by Shekhar R. Biswas. - Biswas, Shekhar Ranjan (2008)
In this thesis I examined three important ecological questions to understand the role of forest management disturbance on unmapped small stream riparian plant communities: I) how do small stream riparian plant communities respond to forest harvesting and site preparations? ii) How do species diversity - functional diversity reiationships vary in disturbed riparian and disturbed upland habitats? and iii) Do riparian buffer reserves act as plant refuges in the clearcut boreal forests? In chapter 1, I answer the first question by reviewing and synthesizing published (searching ISI Web of Knowledge™ database) and grey literature. I found that small stream riparian plant communities are very poorly studied. Forest harvesting and scarification significantly reduce riparian plant species richness and diversity causing a shift from herbaceous to shrub dominance. I suggest that disturbance along small streams may facilitate the spread of invasive species into the streams that are protected by buffer reserve. I argue that the distribution patterns of plant functional traits might be useful as a predictor in developing an early warning system against habitat degradation. In chapter 2, I answer the second question by sampling naturally colonized plants along small streams in clearcut, clearcut plus soil scarification, riparian buffer reserve near clearcut, riparian buffer near clearcut plus soil scarification and uncut reference sites. Using 36 sets of functional traits as a surrogate of functional diversity, I test the effects of disturbance on species diversity - functional diversity relationships in two habitats: riparian and upland, I found that both species diversity and functional diversities reach their peak under moderate intensity of disturbance, producing a bell shaped disturbance-diversity curve. The disturbance-habitat sensitivity coupling has very little effect on overall diversity although the effect on particular life forms and functions may be significant. The novel finding in this study is that in natural communities, species-functional diversity relationships are linear in low intensity disturbance but this relationship shifts to curvilinear (quadratic) with moderate to high intensity of disturbance, due to uneven functional redundancy. This finding invokes that the current approach of conservation that predominantly relies on species richness needs to be reevaluated by considering plant functional traits. In chapter 3, I answer the third question by sampling plant communities around small streams in the clearcuts, the riparian buffer reserves around clearcut and in the uncut reference forests. I used a combination of trait based functional dichotomy and plant cover to predict plant colonization from the clearcuts to riparian buffer reserves. I found that riparian buffer reserves support more species than the clearcuts and the reference forests. In the trait display I was able to show that additional species in riparian buffer reserves were coming from adjacent clearcuts. This finding suggests that in the boreal forest, riparian buffer reserves act as refuges for plants, especially in the early stages after clearcutting. This finding invokes that careful management of riparian buffers may help in reducing the local extinction risk of many disturbance-sensitive plants. Study site : Current River and Mackenzie River Watershed, 30 km. east of Thunder Bay, Northwestern Ontario.